1999
DOI: 10.1073/pnas.96.24.13714
|View full text |Cite
|
Sign up to set email alerts
|

Isopentenyl diphosphate biosynthesis via a mevalonate-independent pathway: Isopentenyl monophosphate kinase catalyzes the terminal enzymatic step

Abstract: In plants, the biosynthesis of isopentenyl diphosphate, the central precursor of all isoprenoids, proceeds via two separate pathways. The cytosolic compartment harbors the mevalonate pathway, whereas the newly discovered deoxyxylulose 5-phosphate pathway, which also operates in certain eubacteria, including Escherichia coli, is localized to plastids. Only the first two steps of the plastidial pathway, which involve the condensation of pyruvate and glyceraldehyde 3-phosphate to deoxyxylulose 5-phosphate followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 36 publications
2
63
0
Order By: Relevance
“…Higher plants contain orthologs of all relevant yeast genes. Genes coding for the enzymes comprising the alternative DXP pathway also are present in higher plants, in agreement with the biochemical evidence of both pathways in green algae and in dicots (Disch et al 1998;Lange et al 1998;Lange and Croteau 1999).…”
Section: Defining the Orthologs: Only Higher Plants Have The Full Comsupporting
confidence: 63%
See 2 more Smart Citations
“…Higher plants contain orthologs of all relevant yeast genes. Genes coding for the enzymes comprising the alternative DXP pathway also are present in higher plants, in agreement with the biochemical evidence of both pathways in green algae and in dicots (Disch et al 1998;Lange et al 1998;Lange and Croteau 1999).…”
Section: Defining the Orthologs: Only Higher Plants Have The Full Comsupporting
confidence: 63%
“…Recently, a role in the DXP pathway has been proposed for another member of this superfamily, called YchB in E. coli (indicated by 12 in Fig. 1), which is capable of forming IPP by phosphorylation of an isopentenyl monophosphate (IMP) precursor, and also phosphorylates the essential intermediate phosphocytidyl-2-C-methylerythritol (Lange and Croteau 1999;Luttgen et al 2000). We found that related sequence motifs are present in diphosphomevalonate decarboxylases.…”
Section: Detailing the Motifs: New Sequence Relationships For Three Ementioning
confidence: 93%
See 1 more Smart Citation
“…5) throughout the GHMP kinase family of phosphotransferases. Moreover, isopentenyl monophosphate kinase also exhibits this motif (23).…”
Section: An Active Site Serine In Mevalonate Kinasementioning
confidence: 99%
“…STC1 was deemed originally to be a sesquiterpene synthase on the basis of the chemical phenotype of stc1 mutants (Shen et al, 2000) and not on the basis of its in vitro product. The presence of a CTP was considered unusual because sesquiterpenes are synthesized in the cytosol via the mevalonic acid pathway, the plastids being the site of synthesis of monoterpenes and diterpenes via the methyl erythritol phosphate or mevalonic acid-independent pathway (Lange and Croteau, 1999). However, natural and engineered exceptions to this compartmentation do occur.…”
Section: Discussionmentioning
confidence: 99%